Pengendalian Kualitas Produk Paving Block untuk Meminimalkan Cacat Menggunakan Six Sigma pada UD. Meurah Mulia - Abdiel Khaleil Akmal; Risnadi Irawan; Khairul Hadi; Heri Tri Irawan; Iing Pamungkas; Kasmawati Kasmawati (Jurnal Optimalisasi, 2021)
A production process will not be free of difficulties with faulty goods during its implementation; this is a problem that is a major factor in the production process; if the process still has many problems with product defects, the process has not been adequately regulated. Moving on from the issues raised above, the author did research at UD. Meurah Mulia, a paving stone manufacturer. For the time being, the control process in the manufacturing process is inspection control, which is an inspection that just distinguishes good and faulty goods without improving the process. In this scenario, the authors advise using the Six Sigma approach to eliminate flaws, which is a process control method that can affect decisions connected to product manufacturing, namely the production and insfection functions. The results of the analysis through processing with the Six Sigma method, which goes through five stages, namely define, measure, analyze, improve, and control, show that the current control process is ineffective, as evidenced by the occurrence of numerous defects in the manufacturing of Paving Blocks.